POSISI BERSAING NENAS DAN PISANG INDONESIA DI PASAR DUNIA - Muhammad Firdaus; Bayu Geo Sandy Silalahi (Departemen Agribisnis, FEM-IPB, 2007)
The production of pineapples and bananas in Indonesia has tended to increase. However, their export value and volume decreased in the period of 1995-2005. This study aims to analyze the competitive position of pineapples and bananas in the international market. The Herfindahl Index (HI) and Concentration Ratio (CRn) were used to investigate the market structure. Revealed Comparative Advantage (RCA) and Porter’s Diamond Theory were used to investigate the comparative and competitive advantages. The result showed that Indonesian pineapple and banana did not have a comparative advantage.